Stability of a concentrated oil-in-water emulsion model prepared using palm olein-based diacylglycerol/virgin coconut oil blends: Effects of the rheological properties, droplet size distribution and microstructure - Ng, Siou Pei; Lai, Oi Ming; Abas, Faridah; Lim, Hong Kwong; Tan, Chin Ping (Elsevier, 2014)
The rheological properties, microstructure, textural properties, colour and droplet size distribution of mayonnaise-like emulsion models prepared using 10–30 wt.% of palm olein-based diacylglycerol (POL-DAG) oil were compared with those of the control (100 wt.% VCO) model. There were significant (P < 0.05) differences in the particle size distribution of the oil droplets, the textural properties, and the rheological properties of the various emulsion models. The rheological analysis included the determination of the flow curves, yield stress, thixotropy, apparent viscosity, and viscoelastic parameters. The concentrated oil-in-water (O/W) emulsion with 30 wt.% POL-DAG substitution exhibited high thixotropy. The POL-DAG content had a substantial effect on the rheological properties of yield stress, storage modulus (G′) and loss modulus (G″). The pseudoplastic behaviour of the emulsions was demonstrated. The size of the particles in the 30% POL-DAG-substituted emulsion was dramatically increased after one day and 30 days of storage. All of the emulsion samples with POL-DAG substituted for VCO showed a relatively non-uniform bimodal droplet size distribution after one day of storage. In general, substitution of 10–20 wt.% POL-DAG oil is appropriate for preparing O/W emulsions that had flow curves and textural properties similar to those of the control sample.